Antidiabetic Agent DPP-4i Facilitates Murine Breast Cancer Metastasis by Oncogenic ROS-NRF2-HO-1 Axis via a Positive NRF2-HO-1 Feedback Loop - Li, Rui; Zeng, Xin; Yang, Meihua; Xu, Xiaohui; Feng, Jinmei; Bao, Liming; Xue, Bingqian; Wang, Xin; Huang, Yi (Frontiers in Oncology, 2021)
Cancer has been as one of common comorbidities of diabetes. Long-term antidiabetic treatment may potentially exert uncertain impacts on diabetic patients with cancer including breast cancer (BC). Dipeptidyl peptidase-4 inhibitors (DPP-4i) are currently recommended by the AACE as first-line hypoglycemic drugs in type 2 diabetes mellitus (T2DM). Although the safety of DPP-4i has been widely evaluated, the potential side-effects of DPP-4i in cancer metastasis were also reported and remains controversial. Here, we revealed that Saxagliptin (Sax) and Sitagliptin (Sit), two common DPP-4i compounds, potentially promoted murine BC 4T1 metastasis in vitro and in vivo under immune-deficient status. Mechanically, we observed that DPP-4i treatment induced aberrant oxidative stress by triggering ROS overproduction, as well as ROS-dependent NRF2 and HO-1 activations in BC cells, while specific inhibition of ROS, NRF2 or HO-1 activations abrogated DPP-4i-driven BC metastasis and metastasis-associated gene expression in vitro. Furthermore, ALA, a NRF2 activator significantly promoted BC metastasis in vitro and in vivo, which can be abrogated by specific HO-1 inhibition in vitro. Moreover, specific HO-1 inhibition not only reversed DPP-4i-induced NRF2 activation, but also abrogated ALA-induced NRF2 activation, resulting in decrease of metastasis-associated genes, indicating a positive-feedback NRF2-HO-1 loop. Our findings suggest that DPP-4i accelerates murine BC metastasis through an oncogenic ROS-NRF2-HO-1 axis via a positive-feedback NRF2-HO-1 loop. Therefore, this study not only offers novel insights into an oncogenic role of DPP-4i in BC progression, but also provides new strategies to alleviate the dark side of DPP-4i by targeting HO-1.